2016
DOI: 10.1007/s40279-016-0590-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hyperoxia on Human Performance and Recovery

Abstract: Hyperoxia results from the inhalation of mixtures of gas containing higher partial pressures of oxygen (O) than normal air at sea level. Exercise in hyperoxia affects the cardiorespiratory, neural and hormonal systems, as well as energy metabolism in humans. In contrast to short-term exposure to hypoxia (i.e. a reduced partial pressure of oxygen), acute hyperoxia may enhance endurance and sprint interval performance by accelerating recovery processes. This narrative literature review, covering 89 studies publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 127 publications
(97 reference statements)
2
64
0
1
Order By: Relevance
“…Specifically, researchers (Mak et al 2002;Gao et al 2012) have found that a 10 min exposure is sufficient to induce physiological responses, which are reversible with Vitamin C, suggesting hyperoxia-induced physiological changes are ROS dependent. As breathing hyperoxic gas during exercise is known to impact performance (Amann et al 2006;Sperlich et al 2016), we limited the exposure to hyperoxia to the pre-exercise period only.…”
Section: Hyperoxic Exposurementioning
confidence: 99%
“…Specifically, researchers (Mak et al 2002;Gao et al 2012) have found that a 10 min exposure is sufficient to induce physiological responses, which are reversible with Vitamin C, suggesting hyperoxia-induced physiological changes are ROS dependent. As breathing hyperoxic gas during exercise is known to impact performance (Amann et al 2006;Sperlich et al 2016), we limited the exposure to hyperoxia to the pre-exercise period only.…”
Section: Hyperoxic Exposurementioning
confidence: 99%
“…This might reflect increased oxidation rates of pyruvate and reduced net glycogen utilization (i.e. anaerobic metabolism), in addition to increased lactate clearance (Hogan, Cox, & Welch, ; Maeda & Yasukouchi, , ; Sperlich et al., ; Stellingwerff et al., ). Although arterial O 2 content and lactate concentrations were not measured in the present study, the similar heart rate and elevated SnormalpO2 observed in the COOL‐HYPER trial (Figure ), along with the similar RPE (Figure ) relative to COOL‐NOR, support an increase in O 2 delivery, central motor output and/or oxidation rate of pyruvate in contributing to the increase in performance.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous studies investigating self‐paced exercise in hot and cool conditions and in hypoxia (Périard & Racinais, , ), in addition to a meta‐analytical review highlighting that the higher power output sustained during hyperoxic time trials elicits a similar RPE to that of normoxic exercise in response to a matching of relative intensity (Mallette et al., ). Future studies could therefore examine the role of intermittent hyperoxic training on high‐intensity self‐paced exercise, particularly given that long‐term adaptations to such training on performance are inconclusive (Sperlich et al., ). A further use for hyperoxia might be during an exercise heat acclimatization regimen to allow for the maintenance of a higher workload within daily sessions, as thermal and cardiovascular strain develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devises such as altitude tents and chambers, on the other hand, are developed to exploit response and adaptation patterns of the organism in which all effects of exposure to hypoxia, both beneficial and non-beneficial, are included (Sperlich et al 2017). This is within the range of 'the natural', or of athletes' 'physiological authenticity'.…”
Section: Ped and 'Natural' Athletic Performancementioning
confidence: 99%